Ferric Carboxymaltose as Treatment in Women with Iron-Deficiency Anemia - Melvin H. Seid; Angelia D. Butcher; Ashwin Chatwani (Anemia)
Objective. To evaluate safety and efficacy of intravenous ferric carboxymaltose (FCM) versus standard medical care (SMC) for iron-deficiency anemia (IDA) in postpartum women and women with heavy menstrual bleeding. Study Design. This open-label, multicenter study randomized women with IDA (hemoglobin ≤ 11.0 g/dL) to single doses of FCM (15 mg/kg [maximum 1000 mg]) or SMC (this treatment was determined by the investigator and there may have been no treatment). Safety data (primary outcome) were collected for 30 days. Results. Of 2045 subjects enrolled (FCM: n=1023; SMC: n=1022), 996 received FCM and 1022 received SMC. At least 1 serious adverse event (AE) was reported by 0.6% and 2.2% of subjects in the FCM and SMC groups, respectively; none were considered treatment related. The difference in serious AEs was primarily due to higher rates of uterine leiomyoma, uterine hemorrhage, and menorrhagia in SMC subjects with heavy menstrual bleeding. Common AEs were generally predictable, with higher rates of infusion site reactions in FCM subjects and gastrointestinal AEs in SMC subjects. Mean hemoglobin increases were greater in the FCM group than the SMC group. Conclusion. FCM was well tolerated and effectively increased mean hemoglobin levels in postpartum women or women with heavy menstrual bleeding and IDA. This trial is registered with ClinicalTrials.gov, NCT00548860.